2005
DOI: 10.1038/sj.npp.1300920
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Lithium Chloride Administration Attenuates Brain NMDA Receptor-Initiated Signaling via Arachidonic Acid in Unanesthetized Rats

Abstract: It has been proposed that lithium is effective in bipolar disorder (BD) by inhibiting glutamatergic neurotransmission, particularly via N-methyl-D-aspartate receptors (NMDARs). To test this hypothesis and to see if the neurotransmission could involve the NMDARmediated activation of phospholipase A 2 (PLA 2 ), to release arachidonic acid (AA) from membrane phospholipid, we administered subconvulsant doses of NMDA to unanesthetized rats fed a chronic control or LiCl diet. We used quantitative autoradiography fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
134
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 106 publications
(151 citation statements)
references
References 132 publications
17
134
0
Order By: Relevance
“…The baseline values of k* for AA in vehicle-treated rats, which ranged from 2.65 to 20.9 × 10 −4 ml/s/g brain, are similar to previously reported values [5,6,8,10,15]. Quinpirole significantly increased k* in 35 regions, many of which belong to dopaminergic circuits containing D 2 receptors (e.g.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…The baseline values of k* for AA in vehicle-treated rats, which ranged from 2.65 to 20.9 × 10 −4 ml/s/g brain, are similar to previously reported values [5,6,8,10,15]. Quinpirole significantly increased k* in 35 regions, many of which belong to dopaminergic circuits containing D 2 receptors (e.g.…”
Section: Discussionsupporting
confidence: 87%
“…In addition to attenuating D 2 -like receptor-mediated AA signaling, chronic lithium, CBZ and valproic acid [6][7][8] each attenuates AA signaling mediated by glutamatergic N-methyl-Daspartate (NMDA) receptors in unanesthetized rats [6,8]. As D 2 -like and NMDA receptors are often functionally coupled and co-localized on the same neurons in brain [52,54], these data suggest that mood stabilizers that are effective against mania suppress AA signaling coupled to both D 2 -like and NMDA receptors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Male CDF-344 rats (weighing 200-215 g, Charles River Laboratories; Wilmington, MA, USA) were randomly assigned to a control group (n = 10) that received vehicle (0.9% saline) once daily for 21 days, and to an NMDA group (n = 10) that received 25 mg/kg NMDA (Sigma Chemical Co., St Louis, MO, USA) once daily for 21 days. The NMDA dose was based on our earlier studies with NMDA in rats [4,14,32]. Three hours after the last saline or NMDA injection, a rat was anesthetized with CO 2 and then decapitated.…”
Section: Animalsmentioning
confidence: 99%
“…Excitotoxicity has been implicated in the pathophysiology of various human brain disorders, including Alzheimer disease [9,10], Parkinson disease [11], Huntington disease [12], schizophrenia [13], and bipolar disorder [14][15][16]. Studies have demonstrated increased concentrations of glutamate and reduced levels of NMDA receptor (NR) subunits in the brain of some of these patients.…”
Section: Introductionmentioning
confidence: 99%